Design point analysis of the turbofan-driven turboelectric distributed propulsion system with boundary layer ingestion. (May 2016) - Liu, Chengyuan; Valencia, Esteban; Teng, Jinfang
The performance benefits of boundary layer ingestion in the case of air vehicles powered by distributed propulsors have been documented and explored extensively by previous study. However, the increased inlet flow distortion and the system total weight would dramatically reduce the expected benefits. In this paper, a novel turboelectric distributed propulsion module on the N3-X airframe has been developed. It includes two direct-shaft-driven turbofans (each drives a free power turbine) and a propulsors array, and therefore both the direct-shaft-driven turbofan and the propulsors unit produce thrust. Secondly, a parametric and quasi two-dimensional study at component and at system level is carried out so that the effects of these two aerodynamic issues over the system performance can be assessed. The figure of merit in this study is the thrust-specific fuel consumption and the system parameters examined are: the thrust split between propulsors and engines, the capture height and the direct-shaft-driven turbofan parameters. Preliminary results found optimum configurations at around 60–90% thrust split ratio, when installation effects were neglected. The final value depends on the propulsor intake pressure loss and the bypass ratio of the propulsion system.